Assessment of electronic patient education materials for adolescent bariatric surgery candidates: An environment scan - Yolanda N. Wang; Alexandra J. Heidl; Patricia M. Angeles; Biagina-Carla Farnesi; Angela S. Alberga; Tamara R. Cohen (Elsevier, 2023)
Objective: Adolescents who opt for metabolic and bariatric surgery (MBS) will use the internet to learn about the procedure. The objective of this study is to assess the suitability of electronic patient education materials (ePEM) of North American centers that perform adolescent bariatric surgery. Methods: Canadian and American bariatric centers that perform adolescent MBS were identified from the Metabolic and Bariatric Surgery Accreditation and Quality Improvement Program and Google web-based searches. Suitability of ePEM for the adolescent readership was evaluated using the Suitability Assessment of Materials (SAM). Results: Sixty-five centers were evaluated from June to July 2020 with 41% citing adolescent specific material. Six percent of the ePEM were evaluated as 'not suitable', 69% were evaluated as 'adequate', and 25% were evaluated as 'superior'. Conclusion: Adequate ePEM scoring was obtained, but centers had little resources tailored to adolescent patients. Further research is needed to evaluate all the resources provided to adolescents (i.e., resources provided by the health team) to ensure the tools are appropriate for the adolescent readership. Innovation: This environmental scan provided insights to ePEM available for adolescents considering MBS.